ナンキョク カンソク ヨウ セツジョウシャ KD601 ノ ソウコウ キロク - 細谷, 昌之; ホソヤ, マサユキ; 荒金, 兼三; アラガネ, カネゾウ; 佐藤, 和郎; サトウ, カズオ; HOSOYA, Masayuki; ARAGANE, Kanezo; SATO, Kazuo (国立極地研究所, 1967)
P(論文) Several test runs of newly-developed oversnow vehicle (Model KD 601) were carried out on the Antarctic continent near Syowa Station in the autumn of 1966. The travelling data recorded by a tachograph and a revograph were analyzed with other supplementary records. In total, 11 days were spent for the test, covering 295 km at an average speed of 10.1 km/h, and the vehicle consumed 343 litres of fuel at an average rate of 0.85 km/l or 1.17 l/km. Total running time of engine was 3822 min, which were divided into two parts 2062 min (54%) for parking and 1760 min (46%) for driving. There was 12% increase or decrease in the fuel consumption depending on the running speed, even when the load was the same and the vehicle ran on the same terrain. departmental bulletin paper